Confucius’ Education Thoughts and Its Influence on Moral Education in China - Gift Muyunda; Lei Yue (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This systematic review aimed at exploring Confucius’ thoughts and influence on moral education in China. The study results show that ancient Chinese educational thoughts of moral education could be said to have three dimensions: goal, main contents, and teaching methods described in this paper. An analysis of the key elements of Confucius' educational thought’s on moral education reveals that the purpose of moral education in ancient China was to cultivate a totally virtuous individual ('Junzi')., while as the concept of benevolence ('Ren') is considered the foundation of Confucius' moral, educational thoughts, while the concept of etiquette ('Li') is the external form of 'Ren.' Both of them are fundamental to Confucius' ideas on moral education. Confucius' moral education includes numerous teaching approaches, such as self-cultivating, individual instruction, enlightenment, and practice, which are presented in this paper. Furthermore, this paper concludes by arguing that Confucius's educational thoughts on moral education provide a significant reference for contemporary education in todays' China and has enduring value for research and practice in contemporary moral education in the 21st century.